2018
DOI: 10.2320/matertrans.maw201805
|View full text |Cite
|
Sign up to set email alerts
|

Features of Crack Size Distribution- and Voltage Probe Spacing-Dependences of Critical Current and <i>n</i>-Value in Cracked Superconducting Tape, Depicted by Simulation

Abstract: Features of the dependence of critical current and n-value on the width of crack size distribution and voltage probe spacing in cracked superconducting tape were investigated by simulation and analysis of the simulation results. From the simulation results, the following features were confirmed. The variation of critical current and n-value with position along the longitudinal direction of the superconducting tape increases with increasing width of crack size distribution for any voltage probe spacing, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Critical current I c (estimated by application of the electrical field criterion E c = 1 µV/cm to the voltage V—current I curve) and n -value (estimated as the index n of the approximated I ∝ I n curve in the electrical field range of E = 0.1~10 µV/cm) are reduced under high electromagnetic and mechanic stresses, as have been reported for the superconducting oxide (such as RE(Y, Sm, Dy, Gd,···)Ba 2 Cu 3 O 7-δ : REBCCO) layer-coated tape [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], and Bi2223 [ 15 , 16 , 17 , 18 , 19 , 20 ]-, MgB 2 [ 21 , 22 , 23 , 24 , 25 ]- and Nb 3 Sn [ 26 , 27 , 28 , 29 , 30 , 31 ]-filamentary types. In this work, we conduct a fundamental study on the influences of cracks in superconducting layer-coated tape on I c .…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Critical current I c (estimated by application of the electrical field criterion E c = 1 µV/cm to the voltage V—current I curve) and n -value (estimated as the index n of the approximated I ∝ I n curve in the electrical field range of E = 0.1~10 µV/cm) are reduced under high electromagnetic and mechanic stresses, as have been reported for the superconducting oxide (such as RE(Y, Sm, Dy, Gd,···)Ba 2 Cu 3 O 7-δ : REBCCO) layer-coated tape [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], and Bi2223 [ 15 , 16 , 17 , 18 , 19 , 20 ]-, MgB 2 [ 21 , 22 , 23 , 24 , 25 ]- and Nb 3 Sn [ 26 , 27 , 28 , 29 , 30 , 31 ]-filamentary types. In this work, we conduct a fundamental study on the influences of cracks in superconducting layer-coated tape on I c .…”
Section: Introductionmentioning
confidence: 64%
“…In this work, we conduct a fundamental study on the influences of cracks in superconducting layer-coated tape on I c . Usually, the cracking takes place non-uniformly, and hence, the I c / n -values vary by specimen [ 3 , 7 , 13 , 18 ] and along the length of the specimen [ 7 , 13 , 14 ]. Not limited to the stress-induced cracks, the non-uniformly distributed defects introduced during the fabrication process also cause a reduction in I c and n -values [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and also discuss the factor that contribute to raise the critical current values of the regions with voltage probe spacing L (= length of the region) under co-existence of a large crack and multiple small cracks in cases B to E. We take up two extreme situations to derive the upper and lower bounds of critical current of region. 12) In one extreme situation (1), the crack size in all sections is the same as that of the largest crack. In this situation (1), the V section I curve is the same in all sections, and the voltage of the region between the voltage probes, given by the sum of the voltage values of the sections, is the upper bound of the voltage, V region, upper .…”
Section: Resultsmentioning
confidence: 99%
“…2024) Also it was found that this phenomenon is induced by the increase in size of the largest crack among all cracks in the region between the voltage probes. 22,23) Furthermore, by using the simulation method, the experimentally observed phenomenon "under coexistence of a large defect and multiple small defects, I c -value is low when the voltage probe spacing is small but it goes up with increasing voltage probe spacing 18) " was reproduced. 24) For analysis of the distributed I c -and n-values of the region/specimen consisting of multiple cracked sections, the authors have been attempting to calculate the upper and lower bounds of I c -and n-values by using the voltage-current curve of the section with the largest crack among all cracks in the region between the voltage probes.…”
Section: Introductionmentioning
confidence: 97%